Tacit Knowledge Affects the Environmental Practice of Populations in Bangkok Metropolis and Vicinity - Patitas, Nicharnan; Phoochinda, Wisakha (Journal of Contemporary Social Sciences and Humanities, 2025)
Bangkok Metropolis and the surrounding area were ranked the 5th worst in the world for the air quality index in 2023. These environmental problems stem from the lack of basic knowledge of the population’s environmental management skills. This research analyzed the Tacit Environmental Knowledge factors affecting the Environmental Management Practice of Populations. This quantitative research study used a questionnaire to collect data from 410 respondents living in the Bangkok Metropolis and the surrounding area. Results showed the highest tacit knowledge of environmental management in The Skills for Saving Water Resources, with an average score x̄ of 0.94. The second was The Conservation of The Environment is a Public Responsibility, with an average score x̄ of 0.89. The lowest tacit knowledge of environmental management was The Contrast Between "Ozone" and "Clean Air", with an average score x̄ of 0.10. The highest practice in environmental management was the Repair Practice, with an average score x̄ of 1.85. The second was Using Energy-Efficient Products Behavior, with an average score x̄ of 1.67, and the lowest practice level was Taking Public Transportation Instead of a Personal Car Behavior, with an average score x̄ of 0.38. Results also showed that the factors affecting Environmental Management Practice by Correlation Analysis including Education, Environmental Learning Pathway, and Tacit Environmental Knowledge positively related to the Environmental Management Practice of Populations, with statistical significance at α = 0.01.